The Factors Influencing the Choice of Takaful by Corporate Policyholders - Majid Nili Ahmad Abadi; Leili Niakan; Mahsa Heidari Ahmadi (تحقیقات مالی اسلامی (پیوسته))
The insurance industry is one of the manifestations of the progress of human societies, which, as one of the basic needs of people, has grown in proportion to the progress of societies. With the introduction of insurance in Muslim societies (takaful), this industry quickly attracted the attention of religious professionals. Therefore, relying on the importance of insurance and its role in supporting the economy of the society and its importance in Iran, this study aims to identify and rank the factors affecting Takaful demand by corporate insurers. The current research is applied in terms of purpose and hybrid in terms of method. All legal insurers including industrial, agricultural and service institutions such as refineries, sports complexes, mines, universities, hospitals, aviation complexes, petrochemicals constitute the statistical population of the research, whose number is 101 corporate policyholders. The sampling method is judgmental, from the type of sample available and the number of samples is 40 corporate policyholders. Questionnaire, interview, library study and document study were used to collect data. The number of primary factors is 3, which are categorized into 7 categories under the headings of innovation and technology, marketing and advertising policy, human resources, financial factors, external and control factors, organizational structure and ideological factors. In order to determine the importance of weighting criteria for companies, the best-worst (BWM) method was used, the TOPSIS method was used to determine the weight of sample insured companies, and the WASPAS-Fuzzy method was used to rank the factors affecting the choice of Takaful insurance. The findings of the research show that ideological factors, the financial ability of companies to fulfill their commitments, the adaptation of external and control factors to customer needs, innovation in Takaful products and services, innovation in Takaful products, the adaptation of the general level of prices compared to conventional insurance, the adaptation of external factors and control with the needs of companies, organizational structure to accept new services, sufficient financial resources to develop and provide services, protection, maintenance and support in providing services, providing a wide range of services, introducing a variety of takaful products, sufficient information of company personnel, identification, persuasion maintenance and provision of services are among the factors affecting Takaful demand by corporate insurers, and ideological factors have had the most direct effect.